2019
DOI: 10.5296/ijhrs.v9i4.15697
|View full text |Cite
|
Sign up to set email alerts
|

Work-Life Balance, Employee Job Performance and Satisfaction Among Doctors and Nurses in Malaysia

Abstract: In this era, the concepts of human resource management (HRM) practices have evolved to the implementation of work-life balance (WLB) practices, such as: flexible working hours and supportive supervision. WLB practices have shown a great influence on employee attraction, retention, motivation and development. This study examines the relationship between WLB practices on employee job performance as well as the mediating effect of job satisfaction in the relationship between work-life balance practices and employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(95 citation statements)
references
References 31 publications
8
54
1
3
Order By: Relevance
“…Therefore, this research empirically confirms that being able choose the order in which one will perform tasks, being able to work at one's own pace and using one's own methods, being consulted about objectives that affect one's work, being able to influence the decisions that are important, or having the opportunity to apply one's own ideas at work, among other discretionary acts, cushions the negative effect that the psychological pressure of nursing work exerts on WLB. These results are in line with the study by Pisarski et al (2006), who show that increased control in the workplace generates better WLB, especially when the individual is able to control his or her work hours and/or experiences an increase in schedule flexibility [112][113][114][115]. For many health professionals, their commitment to their work and professional career is a priority that takes them away from family and social relationships and causes them to dedicate less time than they would like to family responsibilities [116].…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, this research empirically confirms that being able choose the order in which one will perform tasks, being able to work at one's own pace and using one's own methods, being consulted about objectives that affect one's work, being able to influence the decisions that are important, or having the opportunity to apply one's own ideas at work, among other discretionary acts, cushions the negative effect that the psychological pressure of nursing work exerts on WLB. These results are in line with the study by Pisarski et al (2006), who show that increased control in the workplace generates better WLB, especially when the individual is able to control his or her work hours and/or experiences an increase in schedule flexibility [112][113][114][115]. For many health professionals, their commitment to their work and professional career is a priority that takes them away from family and social relationships and causes them to dedicate less time than they would like to family responsibilities [116].…”
Section: Discussionsupporting
confidence: 89%
“…Malaysia has described the shortage of nurses and doctors as a critical issue faced by public hospitals. This issue is worsening due to the shortages of medical professionals and the growing number of patients which leads to a high-intensity of daily clinical routine, such as long working hours and working under time pressure (Cooper et al, 1989;Sibbald et al, 2000;Dousin, Collins & Kler, 2019). A nurse-to-patient ratio of 1:200 is recommended by the World Health Organization (WHO), while the Malaysian nurse ratio at public hospitals is 1:302 (Aris, 2019).…”
Section: The Rationale Of the Researchmentioning
confidence: 99%
“…Studies on WLB in the healthcare sector in western countries are extensive but rarely concentrated on the Asian context, specifically Malaysia. Several studies suggested that workplace practices, policies and support to WLB programs helps to improve employee well-being, organisational commitment, job performance and job satisfaction (Cegarra-Leiva et al, 2012;Dousin et al, 2019;Greenhaus et al, 2003;Haar, 2013;Morganson et al, 2010;Noor, 2011). Work-life conflict will occur due to employees' personal experiences of imbalance between work and personal life.…”
Section: The Relationship Between Work-life Balance and Employee Wellmentioning
confidence: 99%
“…spouse and supervisor support) is seen as a coping mechanism to reduce employees' work-life conflict, improves well-being and their quality of life (Frone et al, 1992;Frone et al, 1997;Greenhaus et al, 1997;Higgins et al, 1992;Parasuraman et al, 1992). Furthermore, a recent study by Dousin et al (2019) revealed that WLB practices and policies could improve employees' job satisfaction which eventually enhances their performance at work. Therefore, WLB practices are an important predictor to employee well-being.…”
Section: The Relationship Between Work-life Balance and Employee Wellmentioning
confidence: 99%